Development Of ESQ Based LKPD On Circulation System Material For SMA/MA - Khairatunnisa Khairatunnisa; Ardi; Syamsurizal; Relsas Yogica; Helsa Rahmatika (LP2M UIN Ambon, 2026)
The objective of the Merdeka Curriculum is to address previous educational issues, which requires appropriate learning media with a supportive model. The learning media commonly used by teachers at Padang 8 State Senior High School is LKPD. The learning model commonly used by teachers at Padang 8 State Senior High School is PBL. However, the LKPD still used by teachers does not yet include cases in the LKPD. The Merdeka Curriculum not only prioritises cognitive values but also spiritual values. All biology materials can be linked to ESQ. LKPD that contains models and is equipped with ESQ will add a spiritual dimension to students. The results of interviews and observations of students show that the material on the circulatory system is difficult to understand. Therefore, PBL-based LKPD with an ESQ nuance was developed for the material on the circulatory system. The research and development (R&D) used a 4-D model that was limited to 3-D, namely define, design, and develop. The research instruments used in this study were interview sheets for teachers, validity test sheets, and practicality test sheets. In the definition stage, data was collected by interviewing one biology teacher and distributing observation sheets to 63 students in Phase F at Padang 8 State Senior High School. The data obtained was then analysed qualitatively and quantitatively. Based on the research results, it can be concluded that the validity test results obtained were 83.31% (highly valid) and the practicality test results obtained by teachers were 93.05% (highly valid), while the results of the practicality test by students obtained 90.33% (highly valid), thus producing a PBL-based LKPD with an ESQ nuance on the subject of the circulatory system for senior high school/MA that is highly valid and highly practical.